2005
DOI: 10.2307/20777574
|View full text |Cite
|
Sign up to set email alerts
|

Public & Private Spillovers, Location and the Productivity of Pharmaceutical Research

Abstract: While there is widespread agreement among economists and management scholars that knowledge spillovers exist and have important economic consequences, researchers know substantially less about the "micro mechanisms" of spillovers-about the degree to which they are geographically localized, for example, or about the degree to which spillovers from public institutions are qualitatively different from those from privately owned firms (Jaffe, 1986; Krugman, 1991; Jaffe et al., 1993; Porter, 1990). In this paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…This provides further evidence of the reasoning behind Hypothesis 3b: programmers can be deployed throughout an organization and learning economies and knowledge can be transmitted across IT projects at different establishments 19 . Some prior research using patent citations has also provided evidence of intra‐firm knowledge spillovers in other settings (e.g., Frost, 2001; Furman et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides further evidence of the reasoning behind Hypothesis 3b: programmers can be deployed throughout an organization and learning economies and knowledge can be transmitted across IT projects at different establishments 19 . Some prior research using patent citations has also provided evidence of intra‐firm knowledge spillovers in other settings (e.g., Frost, 2001; Furman et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Geographic location also plays an important role (e.g., Griliches, 1957). Prior work has demonstrated evidence of localization in innovation (Jaffe et al, 1993), suggesting that a propitious location may lower the costs of innovative output (Furman et al, 2005). It is widely assumed that such concerns have motivated firms in information technology (IT) hardware, software, and pharmaceuticals to cluster together (e.g., Saxenian, 1996; Bresnahan and Gambardella, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Local collaborations need to be large not only in scale but also in scope. In this way, the value for future innovation by learning from foreign technology can be less constrained by the limited absorptive capacity of focal firms (Furman, Kyle, Cockburn, and Henderson, ; van Dijk and Bell, ; Zucker, Darby, and Armstrong, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the significance of spill over effects, notably the diffusion of specialized knowledge among academic and private sector organizations in biomedical clusters, such as those found in Boston or San Diego [3,5]. Spillovers include the exchange of ideas through informal meetings, formal workshops and conferences, and the movement of scientists between companies in a specific geography.…”
Section: Social and Legal Structures That Support Innovationmentioning
confidence: 99%